Features of the work of flat large-span structures - A. K. Yusupov; H. M. Muselemov; R. I. Vishtalov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The purpose of the study is to prove the features of the operation of largespan flat structures, which are also taken into account in their design.Method. A technique is presented that makes it possible to reduce span bending moments. Examples of rational design of beam trusses are given.Result. The given structural diagrams, as well as the analysis of their work, allow designing large-span flat systems in the form of frame and arch structures, which have high reliability, minimal weight, and high manufacturability in manufacturing, transportation and installation.Conclusion. The presented structural schemes, sections and junctions of elements are used in the practice of design and construction. Rational design solutions make it possible to reduce the own weight of flat largespan structures, frames and arches due to the optimal choice of their design and design schemes.